A Report On Outbreak Of Anthrax In Elephant - Yasothai , R.; Shamsudeen , P. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Anthrax is one of the most important zoonotic diseases because of its worldwide distribution with wide host range and tremendous losses due to mortality of animals. In human beings it causes various forms of disease syndrome like malignant carbuncles, wool sorter disease and intestinal anthrax (Chakrabarti, 2005). In India Sharma et al. (1992) reported existence of anthrax in domestic and wild animals but symptomatology is not well described in Indian literature on anthrax in elephants. The present report is based on the outbreak of anthrax in elephant at Thalavadi and Thottakombai forest area of Erode District of Tamilnadu.